Locally recurrent subcutaneous and muscular hydatid cysts of the leg: an unusual case report - Ouakrim, Redouane (Pan Afr Med J, 2015)
We report a rare case of 50-year-old Moroccan woman with local recurrence of a subcutaneous hydatid cyst in proximity to the medial surface of the tibia and another cyst at the tibialis posterior muscle in the absence of liver, lung und spleen involvement. The first surgery was done in another hospital three years ago; no adjuvant treatment was performed after surgery. Recurrence was diagnosed according to the MRI appearance, serological and pathological findings. The patient underwent complete excision of the subcutaneous cyst with two centimeters of the medial gastrocnemius muscle; the tibialis posterior muscle cyst was intraoperatively drained and irrigated with scolicidal agent as it was next to the posterior tibial pedicle. A periopertive anthelmintic chemotherapy was administered. Two years after the patient showed no recurrence. This case report and literature review describe an approach to the diagnosis and management of this pathological entity.